If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -7a = x Combine like terms: 4a + -7a = -3a -3a = x Solving -3a = x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '-3'. a = -0.3333333333x Simplifying a = -0.3333333333x
| (6b-4)(b-8)=0 | | x^2+101=1 | | -1.5x+.5=.66 | | 4(2x+9)-12-2x=20 | | x^2+65=1 | | 9-[-2b+8]=2.8 | | 2n+2.1=4.3 | | 8-6n=-2n | | .50(30x+10)-6(x-2)=28 | | 15X-7Y=1 | | 4a+2b+(-1-a-b)=-11 | | 64x-56=-8y | | X^2+16x+75=0 | | (4o-28)+(o+13)=90 | | X^2+12x+36=81 | | 21x^2=34x+55 | | Y=-16t^2+254 | | 1.6=.83x | | 2n-3=8n+9 | | 7x=90+22 | | (4x+18)=(16x-12) | | 18-2(4x-1)=12 | | (4t+16)+(5t-21)=180 | | 7+2(3x-1)=8x-3(2x+5) | | -3x-2y=17 | | y-32=-10 | | p^2-2pq+q^2=0 | | x^2-6x^2-9= | | 30-6x=6-3x | | Y=X^2+9x+18 | | -16x^2-60x+6=0 | | x^2+16x-78=0 |